TiRiFiG, a graphical 3D kinematic modelling tool - Twum, Samuel Nyarko (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2019)
Galaxy kinematics is of crucial importance to understanding the structure, formation and evolution of galaxies. The studies of mass distributions giving rise to the missing mass problem, first raised by Zwicky (1933), give us an insight into dark matter distributions which are tightly linked to cosmology. Neutral hydrogen (H i) has been widely used as a tracer in the kinematic studies of galaxies. The Square Kilometre Array (SKA) and its precursors will produce large Hi datasets which will require kinematic modelling tools to extract kinematic parameters such as rotation curves. TiRiFiC (JÃ³zsa et al., 2007) is an example of such a tool for 3D kinematic modelling of resolved spectroscopic observations of rotating disks in terms of the tilted-ring model with varying complexities. TiRiFiC can be used to model a large number (20+) of parameters which are set in a configuration file (.def) for its execution. However, manually editing these parameters in a text editor is uncomfortable. In this work, we present TiRiFiG, Tilted Ring Fitting GUI, which is the graphical user interface that provides an easy way for parameter inputs to be modified in an interactive manner.
Keywords: Tilted Ring Fitting GUI; Astronomy -- Observations; Galaxies -- Observations; Galaxies -- Measurement; Galaxies -- Measurement -- Data processing; Kinematics